2019
DOI: 10.2147/ott.s206180
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-155-3p promotes breast cancer progression through down-regulating CADM1</p>

Abstract: Background/purposeCell adhesion molecule 1 (CADM1) functions as a tumor suppressor and has been identified to be frequently inactivated in breast cancer, and closely associated with patients’ poor prognosis and advanced TNM stage. However, the mechanisms underlying CADM1 in breast cancer progression remains incompletely clear. miR-155, a predicted modulator of CADM1 was reported to be overexpressed in breast cancer, and its high expression level was closely related to the malignant progression of breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…miR-155 is previously identified as an oncogenic miRNA in various cancers, such as breast cancer, ovarian cancer and lung cancer. [32][33][34] In our work, we observed that miR-155 was upregulated in both M2 TAMs and exosomes secreted by M2 TAMs. Moreover, the function of exosomes secreted by M2 TAMs in NSCLC metastasis was mediated by miR-155, which modulated RASSF4 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 53%
“…miR-155 is previously identified as an oncogenic miRNA in various cancers, such as breast cancer, ovarian cancer and lung cancer. [32][33][34] In our work, we observed that miR-155 was upregulated in both M2 TAMs and exosomes secreted by M2 TAMs. Moreover, the function of exosomes secreted by M2 TAMs in NSCLC metastasis was mediated by miR-155, which modulated RASSF4 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 53%
“…Most of the selected studies agree with the positive correlation between miR-155 overexpression and tumour grade [10,11], Tumour Node Metastasis stage (TNM) [10,12,19] and LN positivity [10,12,19]. Conversely, some discordances emerge about the miR-155 correlation with hormonal receptor status (ER, PR, and HER2).…”
Section: Tissue Mir-155 Versus Patient-and Tumour-related Prognostic mentioning
confidence: 55%
“…In the same study, the univariate analysis demonstrated that miR-155, tumour grade, TNM stage, LN metastases and c-erbB-2 expression were all significantly associated with poor OS, whereas the multivariate analysis identified miR-155 and LN metastases as independent factors for predicting prognosis in BC patients. Similarly, Zhang et al [19] reported a close association between tissue miR-155 overexpression and shorter OS. Differently, Gasparini et al asserted a protective role for miR-155 in TNBC [15,16].…”
Section: Tissue Mir-155 Versus Prognostic Models and Response To Therapymentioning
confidence: 81%
“…MiR-155 is previously identi ed as an oncogenic miRNA in various cancers, such as breast cancer, ovarian cancer and lung cancer [35][36][37] . In our work, we observed that miR-155 was up-regulated in both M2 TAMs and exosomes secreted by M2 TAMs.…”
Section: Discussionmentioning
confidence: 99%